2012
DOI: 10.1002/mame.201100364
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Filament Fibers – A Review

Abstract: Ceramic fibers are essential components of new high‐temperature‐resistant lightweight materials. The production routes of ceramic filament fibers are complex and in most cases polymeric components or structures are key factors for fiber spinning. Either organic polymers are used as additives in the spinning dopes for oxide ceramic fibers or inorganic polymers are the precursors for the production of non‐oxide fibers. This paper gives an up‐to‐date overview about different ceramic fibers and the chemistry behin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 141 publications
0
42
0
4
Order By: Relevance
“…They are prone to degradation of their strength and embrittlement when subjected to high-thermal loads, which is normally associated with the degradation of the fibers [10][11][12]. Early studies by Wilson [13] showed that the aforementioned fibers present strength loss when tested at temperatures above 1000°C.…”
Section: Introductionmentioning
confidence: 97%
“…They are prone to degradation of their strength and embrittlement when subjected to high-thermal loads, which is normally associated with the degradation of the fibers [10][11][12]. Early studies by Wilson [13] showed that the aforementioned fibers present strength loss when tested at temperatures above 1000°C.…”
Section: Introductionmentioning
confidence: 97%
“…They are supplied by 3M Corporation (Nextel fibers), Sumitomo Corporation (Altex fibers) or Mitsui Mining (Almax fibers) and their cost is relatively low. 14) They are in general used for heat-insulating covers and furnaces. However this type of fibers suffers from grain growth and creep at high temperatures which are limiting factors for long periods of usage.…”
Section: Introductionmentioning
confidence: 99%
“…There, the inorganic block segmentalso referred to as preceramic block segmentis directly converted into the ceramic material after thermal treatment maintaining the block copolymer-templated nanostructure. [48][49][50] More basic requirements for well-defined microphase separation of block copoly-mers are e.g., precise control over blocking efficiency and narrowly distributed polymer masses. [23][24][25][26][27][28][29] All these above mentioned powerful applications based on block copolymers necessitates the precise synthesis of the underlying block copolymer architectures comprising adjustable block length and exact (block) polymer constitution.…”
Section: Introductionmentioning
confidence: 99%